Evocative properties of precedent proper names in the newest German-speaking fictional discourse - Yu. A. Blinova (Вестник Самарского университета: История, педагогика, филология)
The article based on the works of the second decade of the XXI century of the modern German-speaking authors analyses and describes the realization of the evocative function of precedent proper names in the newest German fictional discourse as a mechanism for creation of extra implicit meanings. Precedent names possess the evocative property and act as evocative shifters that allow for shifts between various conceptual fields and actualization of lingua-cultural concepts on the level of content. In the capacity of figurative analogies, metaphors and metonymies they act as evocative triggers, creating implications. Carrying deep associative meaning, they allow for thinking out and speculating about information that is omitted or implied by the authors. Usage of precedent names in fictional discourse is a cultural and intellectual communicative strategy that allows authors to control the perception and interpretation of the information read. Thus they can be considered as markers for both culturally important and implicit types of information. In general, precedent names realize the tendencies for implicity, fascinativity and suggestivity that contribute to the increase in expressiveness, emotionality and aesthetic impact of a fictional text.